MODERN APPROACH TO THE DIAGNOSIS AND TREATMENT OF CYSTIC PREGNANCY (REVIEW) - M. S. Salomov; G. E. Bekmirzayeva (Web of Journals Publishing, 2025)
Gestational trophoblastic disease (GTD) is a group of conditions that occur in pregnant women as a result of abnormal trophoblastic proliferation. It includes benign (complete and partial hydatidiform moles) and malignant (so-called gestational trophoblastic neoplasia) conditions. Geographic heterogeneity in the distribution of GTD has been statistically noted. While these data suggest the importance of ethnicity, the true causes may be directly related to diet, diagnostic quality, population coverage, and differences in statistical data recording.
Keywords: Hydatidiform mole, trophoblastic disease, gestational diseases.